(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Childhood obesity is one of the most important health problems prevalent in all countries of the world, as many studies conducted in most countries of the world indicate that there is a marked increase in the prevalence of obesity and overweight among children in various societies, and the reports of the World Health Organization have indicated an increase Disturbing in the rate of obesity in children in early childhood, as it has become a global epidemic, according to the description of the World Health Organization [1]. It was found that about 40 million children under the age of five suffer from overweight and obesity, as the percentage of children who suffer from obesity increased in age (5 to 19) years old from 1 in 10 children in 2000 to approximately 1 in 5 children in 2016. [4]The causes of obesity are many and varied, and the possibility of a child being exposed to the risk of being overweight and obese is due to the overlap of many biological and environmental factors. It is well known that maintaining the normal weight of the body requires a balance between the thermal energy entering the body (through food) and the heat energy consumed (through the energy consumed in each of the basic vital processes, represented in the digestion and absorption of food, as a result of carrying out the usual daily activities. Including physical activities and sports, and this adds the energy needed for growth in pre-adulthood. [3]. The importance of the research lies in identifying the most important factors causing obesity in children whose ages range from 5 to 14 years, through the use of a factor analysis method that revealed the presence of 5 main factors that had a clear effect on childhood overweight and obesity.